Modified chromium carbide-based metal ceramic coating as well as preparation method and application thereof

By forming micron-sized micropores on the surface of the chromium carbide-based metal ceramic coating and filling it with a composite high-temperature lubricating phase, the problem of easy failure of lubricants in high-temperature environments is solved, low friction coefficient and anti-wear performance in a wide temperature range are achieved, and the tribological properties and service life of the coating are improved.

CN120738593AActive Publication Date: 2025-10-03GUANGDONG INST OF NEW MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511148996.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-10-03
Estimated Expiration
2045-08-18

AI Technical Summary

Technical Problem

Existing lubricants are prone to failure in high-temperature environments, causing the friction pair to directly contact the substrate, causing severe wear and affecting the service life of the workpiece. Traditional lubricants also affect the mechanical properties and wear resistance of the material.

Method used

Micron-sized micropores are formed on the surface of the chromium carbide-based metal ceramic coating, and a composite high-temperature lubricating phase mixture, including barium fluoride, calcium fluoride, hexagonal boron nitride, graphite, boron oxide, bismuth oxide, Ag, Cu, MoS2 and WS2, is filled in through a high-temperature vacuum negative pressure impregnation process to form a wide temperature range lubricating coating.

Benefits of technology

It achieves low-friction coefficient lubrication performance in the range of 25℃~800℃, significantly improves the tribological properties of traditional chromium carbide-based metal ceramic coatings, and enhances the wide-temperature range lubrication life and anti-wear performance of the coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120738593A_ABST
    Figure CN120738593A_ABST
Patent Text Reader

Abstract

The invention discloses a modified chromium carbide-based metal ceramic coating as well as a preparation method and application thereof, and belongs to the technical field of coating materials. The preparation method of the coating comprises the following steps: carrying out surface texture pretreatment on a metal base material with the chromium carbide-based metal ceramic coating to form micron-sized micropores; and coating the composite high-temperature lubricating phase mixture on the surface of the chromium carbide-based metal ceramic coating with micron-sized micropores, melting the composite high-temperature lubricating phase mixture in a high-temperature vacuum negative-pressure impregnation manner, and filling the micron-sized micropores with the molten composite high-temperature lubricating phase mixture. The preparation method is simple and easy to operate, and the prepared modified chromium carbide-based metal ceramic coating has good wear resistance and friction reduction performance, shows excellent lubricating performance with a low friction coefficient through a multi-cycle tribological performance test at the temperature of 25-800 DEG C, and can be widely applied to the field of metal ceramics. The wide-temperature-range tribological performance of a traditional chromium carbide-based metal ceramic coating is greatly improved, and an innovative solution is provided for the life prolonging design of high-temperature moving parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating materials, and in particular to a modified chromium carbide-based metal ceramic coating and a preparation method and application thereof. Background Art

[0002] With the rapid development of industries such as aerospace, marine engineering, and new energy, high-temperature wear of key moving components, such as gas turbine transmission bearings and aircraft engine blades, is becoming increasingly prominent, seriously impacting the service life of the components. Lubricant films on traditional materials are prone to failure in high-temperature environments, leading to severe wear of the friction pair in direct contact with the substrate. This makes wide-temperature lubrication modification of the friction interface particularly important.

[0003] At present, most engineering moving parts use doped liquid lubricants or solid lubricants to improve lubrication performance. However, liquid lubricants are highly volatile and have poor load-bearing capacity, especially in high-temperature environments exceeding 400°C, where they will quickly fail. Traditional solid lubricants are easily oxidized in high-temperature environments above 500°C, and their lubrication performance drops sharply. In addition, the addition of the lubricating phase affects the overall mechanical properties of the material, resulting in a decrease in wear resistance. Therefore, how to achieve the dynamic response of the lubricating phase and the stable load-bearing of the supporting phase in high-temperature wear-resistant coatings over a wide temperature range remains a difficulty and hot topic in current research.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The purpose of the present invention is to provide a modified chromium carbide-based metal ceramic coating and its preparation method and application, so as to solve or improve the above technical problems.

[0006] The present invention can be achieved like this: In a first aspect, the present invention provides a method for preparing a modified chromium carbide-based cermet coating, comprising the following steps: Performing surface texturing pretreatment on a metal substrate having a chromium carbide-based cermet coating to form micron-sized micropores on the surface of the chromium carbide-based cermet coating; The composite high-temperature lubricating phase mixture is applied to the surface of a chromium carbide-based cermet coating having micron-sized micropores, and the composite high-temperature lubricating phase mixture is melted by a high-temperature vacuum negative pressure impregnation method so that at least a portion of the composite high-temperature lubricating phase mixture is filled into the micron-sized micropores; The composite high-temperature lubricating phase mixture comprises a high-temperature lubricating phase and the above-mentioned medium- and low-temperature lubricating phase in a mass ratio of 7.5:2.5 to 8.5:1.5; wherein the high-temperature lubricating phase comprises at least one of barium fluoride, calcium fluoride, and hexagonal boron nitride; and the medium- and low-temperature lubricating phase comprises at least two of graphite, boron oxide, bismuth oxide, Ag, Cu, MoS2, and WS2; The conditions for high-temperature vacuum negative pressure impregnation include: temperature of 500°C~1000°C, vacuum degree of -0.5MPa~-0.01MPa.

[0007] In an optional embodiment, the preparation of the metal substrate having the chromium carbide-based cermet coating includes: preparing the chromium carbide-based cermet coating on the surface of the metal substrate by a thermal spraying process; Among them, the thermal spraying process includes a low-pressure plasma spraying process, an atmospheric plasma spraying process, a supersonic plasma spraying process or a supersonic flame spraying process.

[0008] In an optional embodiment, the thermal spraying process adopts a supersonic flame spraying process, and the process conditions include: oxygen flow rate of 800L / min~1000L / min, kerosene flow rate of 20L / min~40L / min, carrier gas flow rate of 4L / min~12L / min, and powder feeding rate of 50g / min~120g / min.

[0009] In an optional embodiment, the surface texturing pretreatment method includes at least one of nanosecond laser processing, picosecond laser processing, femtosecond laser processing, cutting processing and chemical etching.

[0010] In an optional embodiment, the surface texturing pretreatment includes at least one of the following features: Feature 1: Surface texturing pretreatment is performed using nanosecond laser processing. The process conditions include: laser power of 150W~200W, wavelength of 900nm~1100nm, scanning speed of 800mm / s~1000mm / s, and laser irradiation intensity of 0.1J / mm 2 ~0.3J / mm 2 , the process gas includes nitrogen; Feature 2: The center distance between two adjacent micron-sized micropores is 500μm~1000μm; Feature 3: The longitudinal depth of the micron-sized pores is 40 μm to 80 μm.

[0011] In an optional embodiment, the particle size of the composite high-temperature lubricating phase mixture is 1 μm to 10 μm.

[0012] In a second aspect, the present invention provides a modified chromium carbide-based metal ceramic coating prepared by the preparation method of any one of the aforementioned embodiments.

[0013] In a third aspect, the present invention provides a component having the modified chromium carbide-based metal ceramic coating of the aforementioned embodiment.

[0014] In an optional embodiment, the thickness of the chromium carbide-based cermet coating is 100 μm to 300 μm.

[0015] In a fourth aspect, the present invention provides an application of a component according to the aforementioned embodiment in a wear-reducing and wear-resistant mechanical structure.

[0016] The beneficial effects of the present invention include: The present invention pre-textures the metal substrate with a chromium carbide-based cermet coating. The micron-sized pores formed on the surface of the chromium carbide-based cermet coating can effectively store the wear debris generated during the friction process, thereby reducing friction. Furthermore, the micron-sized pores can effectively store lubricant. The lubricant impregnated into the micron-sized pores can be continuously extruded during the subsequent service of the product, further optimizing the friction interface. The present invention uses a composite high-temperature lubricating phase mixture to fill the micron-sized pores through a high-temperature vacuum negative pressure impregnation process, resulting in a high-load-bearing, wear-resistant lubricating coating with wide-temperature lubrication. This significantly improves the tribological properties of traditional chromium carbide-based cermet coatings in a wide temperature range and increases the wide-temperature lubrication life of the coating.

[0017] The modified chromium carbide-based metal ceramic coating prepared by the above method has both good anti-wear and friction reduction properties. After multi-cycle tribological performance tests at 25°C~800°C, it shows excellent lubrication performance with a low friction coefficient, which greatly improves the wide temperature range tribological performance of traditional chromium carbide-based metal ceramic coatings and provides an innovative solution for the life extension design of high-temperature moving parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 is the XRD pattern of Cr3C2-NiCr powder and Cr3C2-NiCr coating in Experimental Example 1; Figure 2 SEM and EDS images of the Cr3C2-NiCr coating in Experimental Example 1; Figure 3 The SEM and EDS images of the composite high-temperature lubricating phase mixture in the modified chromium carbide-based cermet coating in Experimental Example 1; Figure 4 This is the XPS graph of the surface of the modified chromium carbide-based cermet coating in Experimental Example 1; Figure 5 The SEM and EDS images of the surface of the modified chromium carbide-based cermet coating in Experimental Example 1; Figure 6Friction curves of the modified chromium carbide-based cermet coating of Example 1 in Test Example 2 at different friction cycle times at 25°C to 800°C; Figure 7 This is the friction curve of the modified chromium carbide-based cermet coating of Example 6 in Test Example 2 after four cycles at 25°C to 800°C; Figure 8 This is the friction curve of the modified chromium carbide-based cermet coating of Comparative Example 1 in Test Example 2 after four cycles at 25°C to 800°C; Figure 9 This is the friction curve of the modified chromium carbide-based cermet coating of Comparative Example 2 in Test Example 2 after four cycles at 25°C to 800°C; Figure 10 This is the friction curve of the modified chromium carbide-based metal ceramic coating of Comparative Example 3 in Experimental Example 2 after four cycles at 25°C~800°C. DETAILED DESCRIPTION

[0020] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.

[0021] The modified chromium carbide-based metal ceramic coating provided by the present invention and its preparation method and application are described in detail below.

[0022] The present invention provides a method for preparing a modified chromium carbide-based metal ceramic coating, comprising the following steps: S1: performing surface texturing pretreatment on a metal substrate having a chromium carbide-based cermet coating to form micron-sized micropores on the surface of the chromium carbide-based cermet coating.

[0023] In some optional embodiments, the preparation of the metal substrate having the chromium carbide-based cermet coating may include: preparing the chromium carbide-based cermet coating on the surface of the metal substrate using a thermal spraying process.

[0024] The thermal spraying process may illustratively but not limitatively include a low-pressure plasma spraying process, an atmospheric plasma spraying process, a supersonic plasma spraying process, or a supersonic flame spraying process.

[0025] In some typical embodiments, the thermal spraying process employs a supersonic flame spraying process. The process conditions for the supersonic flame spraying process may include: an oxygen flow rate of 800 L / min to 1000 L / min, a kerosene flow rate of 20 L / min to 40 L / min, a carrier gas flow rate of 4 L / min to 12 L / min, and a powder feed rate of 50 g / min to 120 g / min.

[0026] The oxygen flow rate may be 800 L / min, 850 L / min, 900 L / min, 950 L / min or 1000 L / min, or other values ​​within the range of 800 L / min to 1000 L / min.

[0027] The kerosene flow rate may be 20 L / min, 25 L / min, 30 L / min, 35 L / min or 40 L / min, or other values ​​within the range of 20 L / min to 40 L / min.

[0028] The above oxygen flow rate and kerosene flow rate mainly affect the melting degree of the powder in the flame.

[0029] The carrier gas flow rate can be 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min or 12 L / min, or other values ​​within the range of 4 L / min to 12 L / min.

[0030] The aforementioned carrier gas flow rate directly affects the degree of heating of the powder in the flame, significantly impacting the coating's microstructure, mechanical properties, chemical stability, and spraying efficiency. If the carrier gas flow rate is less than 4 L / min, the powder will remain in the flame for a relatively long time, potentially leading to excessive melting or even burnout of the powder due to overheating (e.g., increased oxidation of easily oxidizable materials), resulting in coarse grains and increased brittleness in the coating. If the carrier gas flow rate is higher than 12 L / min, the fuel and oxygen in the flame will be diluted, lowering the flame temperature while shortening the powder's residence time in the high-temperature zone. This can lead to incomplete powder melting (even a "semi-solid" state), the formation of unmelted particles in the coating, and increased porosity.

[0031] The powder feeding rate may be 50 g / min, 60 g / min, 70 g / min, 80 g / min, 90 g / min, 100 g / min, 110 g / min or 120 g / min, or other values ​​within the range of 50 g / min to 120 g / min.

[0032] The powder feed rate affects both the deposition effect and deposition efficiency of the chromium carbide-based cermet coating. Improper powder feed rate settings can easily lead to high porosity and even defects such as cracks in the chromium carbide-based cermet coating.

[0033] In some optional embodiments, the porosity of the chromium carbide-based cermet coating does not exceed 1%.

[0034] In some optional embodiments, the chromium carbide-based cermet coating on the surface of the metal substrate is first polished and cleaned, and then subjected to surface texturing pretreatment.

[0035] In some optional embodiments, the surface texturing pretreatment method may illustratively but not limitatively include at least one of nanosecond laser processing, picosecond laser processing, femtosecond laser processing, cutting processing, and chemical etching.

[0036] In some limited embodiments, the surface texturing pretreatment is performed by nanosecond laser treatment. The process conditions of the nanosecond laser treatment may include: laser power of 150W to 200W, wavelength of 900nm to 1100nm, scanning speed of 800mm / s to 1000mm / s, laser irradiation intensity of 0.1J / mm 2 ~0.3J / mm 2 , the process gas includes nitrogen.

[0037] The laser power may be 150W, 160W, 170W, 180W, 190W or 200W, or other values ​​within the range of 150W to 200W.

[0038] The wavelength may be 900 nm, 950 nm, 1000 nm, 1050 nm or 1100 nm, or other values ​​within the range of 900 nm to 1100 nm.

[0039] The scanning speed may be 800 mm / s, 850 mm / s, 900 mm / s, 950 mm / s or 1000 mm / s, or other values ​​within the range of 800 mm / s to 1000 mm / s.

[0040] Laser irradiation intensity can be 0.1J / mm 2 , 0.15J / mm 2 , 0.2J / mm 2 , 0.25J / mm 2 or 0.3J / mm 2 etc., can also be 0.1J / mm 2 ~0.3J / mm 2 Other values ​​within the range.

[0041] Laser power can affect the processing accuracy of textured micropores. If the laser power is lower than 150W, the coating material will not be completely vaporized, which can easily lead to the micropores not forming. If the laser power is higher than 200W, the coating material will be over-burned, affecting the texture morphology.

[0042] In the present invention, the shape of the micron-sized micropores obtained by surface texturing pretreatment is not limited, and can be set to circular, rectangular, triangular, polygonal or other irregular shapes as required.

[0043] In some optional embodiments, the micron-sized micropores on the surface of the chromium carbide-based cermet coating are regularly arranged; in other optional embodiments, the micron-sized micropores on the surface of the chromium carbide-based cermet coating may also be irregularly arranged. In some more typical embodiments, the micron-sized micropores on the surface of the chromium carbide-based cermet coating are regularly arranged.

[0044] In some optional embodiments, the center distance between two adjacent micron-sized micropores can be 500μm~1000μm, such as 500μm, 550μm, 600μm, 650μm, 700μm, 750μm, 800μm, 850μm, 900μm, 950μm or 1000μm, etc., or it can be other values ​​within the range of 500μm~1000μm.

[0045] The center distance between the two adjacent micron-sized micropores can characterize the distribution density of micron-sized micropores on the surface of the chromium carbide-based metal ceramic coating. It should be noted that if the center distance between the two adjacent micron-sized micropores is smaller, it means that the number of micron-sized micropores set on the surface of the chromium carbide-based metal ceramic coating is greater, which is more conducive to accommodating more composite high-temperature lubricating phase mixtures to improve lubrication performance; but at the same time, the quality of the chromium carbide-based metal ceramic coating will be reduced, resulting in a smaller supporting force for the entire modified chromium carbide-based metal ceramic coating. The present invention specifically controls the center distance between the two adjacent micron-sized micropores to 500μm~1000μm, which can ensure lubricity while also taking into account appropriate supporting force.

[0046] In some optional embodiments, the longitudinal depth of the micron-sized micropores can be 40 μm to 80 μm, such as 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm or 80 μm, or other values ​​within the range of 40 μm to 80 μm.

[0047] Similarly, a deeper micron-sized pore depth allows for greater accommodating capacity for the composite high-temperature lubricating phase mixture, improving lubrication performance. However, this also reduces the quality of the chromium carbide-based cermet coating, resulting in a decrease in the supporting force of the modified chromium carbide-based cermet coating. The present invention specifically sets the micron-sized pore depth to 40 to 80 μm, ensuring both lubricity and adequate supporting force.

[0048] As mentioned above, the micron-sized pores formed on the surface of the chromium carbide-based metal ceramic coating can effectively store the wear debris generated during the friction process, thereby reducing friction; it can also effectively store lubricants. The lubricants impregnated into the micron-sized pores can be continuously squeezed out during the subsequent service of the product, further optimizing the friction interface.

[0049] S2: applying the composite high-temperature lubricating phase mixture to the surface of the chromium carbide-based metal ceramic coating having micron-sized pores, melting the composite high-temperature lubricating phase mixture by high-temperature vacuum negative pressure impregnation, and filling at least a portion of the composite high-temperature lubricating phase mixture into the micron-sized pores.

[0050] In some optional embodiments, the particle size of the composite high-temperature lubricating phase mixture can be 1 μm to 10 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc., or other values ​​within the range of 1 μm to 10 μm.

[0051] In some optional embodiments, the composite high-temperature lubricating phase mixture includes at least a medium-low temperature segment lubricating phase, which may exemplarily include at least two of graphite, boron oxide, bismuth oxide, Ag, Cu, MoS2, and WS2.

[0052] In some typical embodiments, the lubricating phase in the medium and low temperature range includes graphite, boron oxide, and bismuth oxide. Among them, boron oxide and bismuth oxide have excellent high-temperature stability and high-temperature oxidation resistance. It should be noted that the inventors have creatively discovered that the combination of graphite with boron oxide and bismuth oxide as low-melting-point oxides can play a synergistic role in lubrication and friction reduction. Moreover, at high temperatures, the low-melting-point oxides are in a glassy molten state and have a significant high-temperature oxidation resistance effect. They can encapsulate the refractory lubricating phase particles (such as incompletely melted bismuth oxide and fluoride, etc.) and stably exist in the microporous structure on the surface of the chromium carbide-based metal ceramic coating. They provide effective high-temperature oxidation protection to the refractory lubricating phase particles encapsulated inside, thereby ensuring their effective lubrication at higher temperature ranges.

[0053] In other alternative embodiments, the composite high-temperature lubricating phase mixture may include a high-temperature lubricating phase and a medium-low temperature lubricating phase in a mass ratio of 7.5:2.5 to 8.5:1.5. For example, the mass ratio of the high-temperature lubricating phase to the medium-low temperature lubricating phase may be 7.5:2.5, 8:2, or 8.5:1.5, or may be other values ​​within the range of 7.5:2.5 to 8.5:1.5. The high-temperature lubricating phase may illustratively include at least one of barium fluoride, calcium fluoride, and hexagonal boron nitride.

[0054] In some optional embodiments, the mixing method of the lubricating phases contained in the composite high-temperature lubricating phase mixture is not limited, and can be, for example, at least one of mechanical dry grinding, mechanical wet grinding, and semi-dry grinding. In some more typical embodiments, the mixing method of the lubricating phases contained in the composite high-temperature lubricating phase mixture is mechanical dry grinding.

[0055] In some preferred embodiments, each micron-sized pore is filled with a composite high-temperature lubricating phase mixture.

[0056] In some optional embodiments, the conditions for high-temperature vacuum negative pressure impregnation may include: a temperature of 500° C. to 1000° C. and a vacuum degree of -0.5 MPa to -0.01 MPa.

[0057] The temperature of the high-temperature vacuum negative pressure impregnation may be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, or other values ​​within the range of 500°C to 1000°C.

[0058] The vacuum degree of the high-temperature vacuum negative pressure impregnation may be -0.5 MPa, -0.4 MPa, -0.3 MPa, -0.2 MPa, -0.1 MPa, -0.05 MPa or -0.01 MPa, etc., or other values ​​within the range of -0.5 MPa to -0.01 MPa.

[0059] The high-temperature vacuum negative pressure impregnation time is not limited, as long as the composite high-temperature lubricating phase mixture can be impregnated into the micron-sized micropores. For example, the high-temperature vacuum negative pressure impregnation time can be 10 minutes to 5 minutes, such as 10 minutes, 30 minutes, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, or 5 hours.

[0060] The high temperature vacuum negative pressure impregnation can be performed by coating the composite high temperature lubricating phase mixture on the surface of the chromium carbide-based metal ceramic coating with micron-sized micropores, placing it in a high temperature vacuum muffle furnace, and impregnating it under high temperature and vacuum conditions.

[0061] The degree of vacuum significantly affects the impregnation of the glassy lubricating phase. If the vacuum is less than -0.5 MPa, the glassy lubricating phase may not be fully filled into the microporous structure of the coating surface. If the vacuum is higher than -0.01 MPa, the evacuation time will be increased, significantly increasing the sample preparation cost.

[0062] Continuing from the above, the present invention adopts a compound mixture of multiple substances as a composite high-temperature lubricating phase mixture, and then fills the composite lubricant into micron-sized micropores through a high-temperature vacuum negative pressure impregnation process, thereby obtaining a high-load-bearing wear-resistant lubricating coating with a wide temperature range lubrication effect, greatly improving the tribological properties of traditional chromium carbide-based metal ceramic coatings under a wide temperature range, and increasing the wide temperature range lubrication life of the coating.

[0063] Correspondingly, the present invention also provides a modified chromium carbide-based metal ceramic coating, which is prepared by the above preparation method.

[0064] The modified chromium carbide-based metal ceramic coating has both good anti-wear and friction reduction properties. After multiple cycles of friction in the range of 25°C to 800°C, the friction coefficient can be below 0.2.

[0065] In addition, the present invention also provides a component having the modified chromium carbide-based metal ceramic coating.

[0066] In some optional embodiments, the thickness of the chromium carbide-based cermet coating may be 100 μm to 300 μm, such as 100 μm, 150 μm, 200 μm, 250 μm or 300 μm, or other values ​​within the range of 100 μm to 300 μm.

[0067] In addition, the present invention also provides an application of the above-mentioned component in a mechanical structure with wide temperature range, wear reduction and resistance.

[0068] The features and performance of the present invention are further described in detail below with reference to the embodiments.

[0069] Example 1 This embodiment provides a modified chromium carbide-based cermet coating, the preparation method of which includes: S11: Preparing a metal substrate with a chromium carbide-based cermet coating.

[0070] A Cr3C2-NiCr coating was deposited on a 316L stainless steel substrate using a high-velocity flame spraying process. Commercially available Cr3C2-NiCr powder (particle size 21-54 μm, purchased from Höganäs Ltd, Sweden) was used as the spraying material. The Cr3C2-NiCr coating had a thickness of 200 μm. The HVOF spraying process conditions included an oxygen flow rate of 900 L / min, a kerosene flow rate of 30 L / min, a carrier gas flow rate of 8 L / min, and a powder feed rate of 100 g / min.

[0071] S12: Surface texture pretreatment.

[0072] The Cr3C2-NiCr coating was polished to a roughness of 0.2 μm and then ultrasonically cleaned to remove contamination and wear debris caused by the polishing process. Round micron-sized micropores were prepared on the surface of the chromium carbide-based cermet coating using nanosecond laser treatment. The process conditions for nanosecond laser treatment included: laser power of 180 W, wavelength of 1064 nm, scanning speed of 900 mm / s, and laser irradiation intensity of 0.15 J / mm. 2 The processing gas is nitrogen. The center distance between two adjacent micron-sized micropores is 800 μm, and the longitudinal depth of the micron-sized micropores is 60 μm.

[0073] S21: applying a uniformly mixed composite high-temperature lubricating phase mixture with a particle size of 1 μm to 10 μm to the surface of a chromium carbide-based metal ceramic coating having micron-sized micropores.

[0074] Among them, the composite high-temperature lubricating phase mixture is obtained by mechanically mixing graphite, boron oxide and bismuth oxide powder (particle size of 1μm~5μm, purchased from Höganäs Ltd, Sweden) in a mass ratio of 3:3:4.

[0075] S22: The composite high-temperature lubricating phase mixture is heated to a molten state by a high-temperature vacuum negative pressure impregnation method, and is impregnated into micron-sized micropores using negative pressure to obtain a modified chromium carbide-based metal ceramic coating (Cr3C2-NiCr-B2O3 / Bi2O3 / C composite coating).

[0076] The process conditions of high-temperature vacuum negative pressure impregnation include: temperature of 800°C, vacuum degree of -0.1MPa, and vacuum impregnation time of 3h.

[0077] Example 2 The difference between this embodiment and embodiment 1 is that: In S11, the supersonic flame spraying process conditions include: oxygen flow rate of 800 L / min, kerosene flow rate of 20 L / min, carrier gas flow rate of 4 L / min, and powder feeding rate of 50 g / min. The thickness of the Cr3C2-NiCr coating is 100 μm.

[0078] In S12, the process conditions of nanosecond laser treatment include: laser power of 150W, wavelength of 900nm, scanning speed of 800mm / s, laser irradiation intensity of 0.1J / mm 2 The processing gas is nitrogen. The center distance between two adjacent micron-sized micropores is 500 μm, the longitudinal depth of the micron-sized micropore is 40 μm, and the cross-sectional shape of the micron-sized micropore is rectangular.

[0079] In S21, the composite high-temperature lubricating phase mixture was obtained by mechanically mixing graphite, boron oxide, and bismuth oxide powders (particle size of 1 μm~5 μm, purchased from Höganäs Ltd, Sweden) in a mass ratio of 1:4:5.

[0080] In S22, the process conditions of high-temperature vacuum negative pressure impregnation include: temperature of 500° C., vacuum degree of -0.5 MPa, and vacuum impregnation time of 10 min.

[0081] Example 3 The difference between this embodiment and embodiment 1 is that: In S11, the supersonic flame spraying process conditions include: oxygen flow rate of 1000 L / min, kerosene flow rate of 40 L / min, carrier gas flow rate of 12 L / min, and powder feeding rate of 120 g / min. The thickness of the Cr3C2-NiCr coating is 300 μm.

[0082] In S12, the process conditions of nanosecond laser treatment include: laser power of 200W, wavelength of 1100nm, scanning speed of 1000mm / s, laser irradiation intensity of 0.3J / mm 2 The processing gas is nitrogen. The center distance between two adjacent micron-sized micropores is 1000 μm, the longitudinal depth of the micron-sized micropore is 80 μm, and the cross-sectional shape of the micron-sized micropore is triangular.

[0083] In S21, the composite high-temperature lubricating phase mixture was obtained by mechanically mixing graphite, boron oxide, and bismuth oxide powders (particle size of 1 μm~5 μm, purchased from Höganäs Ltd, Sweden) in a mass ratio of 2:3:5.

[0084] In S22, the process conditions of high-temperature vacuum negative pressure impregnation include: temperature of 1000° C., vacuum degree of -0.01 MPa, and vacuum impregnation time of 5 hours.

[0085] Example 4 The difference between this embodiment and embodiment 1 is that the composite high-temperature lubricating phase mixture consists only of graphite and boron oxide, and the total amount of the composite high-temperature lubricating phase mixture and the amount of graphite used are the same as those in embodiment 1.

[0086] Example 5 The difference between this embodiment and embodiment 1 is that the composite high-temperature lubricating phase mixture consists only of graphite and bismuth oxide, and the total amount of the composite high-temperature lubricating phase mixture and the amount of graphite used are the same as those in embodiment 1.

[0087] Example 6 The difference between this embodiment and embodiment 1 is that the composite high-temperature lubricating phase mixture consists only of boron oxide and bismuth oxide, and the total amount of the composite high-temperature lubricating phase mixture and the amount of boron oxide used are the same as those in embodiment 1.

[0088] Example 7 This example differs from Example 1 in that the composite high-temperature lubricating phase mixture comprises a high-temperature lubricating phase and a medium-low-temperature lubricating phase in a mass ratio of 8:2. The medium-low-temperature lubricating phase comprises graphite, boron oxide, and bismuth oxide powders (particle size 1 μm to 5 μm, purchased from Höganäs Ltd, Sweden) in a mass ratio of 3:3:4, while the high-temperature lubricating phase comprises barium fluoride.

[0089] Comparative Example 1 This comparative example is a metal substrate having a chromium carbide-based cermet coating prepared in S11 in Example 1.

[0090] Comparative Example 2 The difference between this comparative example and Example 1 is that the surface texture pretreatment of S12 is not performed.

[0091] Comparative Example 3 The difference between this comparative example and Example 1 is that the lubricating phase is only graphite, and the total amount of the lubricating phase is the same as that in Example 1.

[0092] Comparative Example 4 The difference between this comparative example and Example 1 is that the powder feeding rate of the supersonic flame spraying is 40 g / min.

[0093] Comparative Example 5 The difference between this comparative example and Example 1 is that the powder feeding rate of the supersonic flame spraying is 150 g / min.

[0094] Comparative Example 6 The difference between this comparative example and Example 1 is that the center distance between two adjacent micron-sized microholes is 400 μm.

[0095] Comparative Example 7 The difference between this comparative example and Example 1 is that the center distance between two adjacent micron-sized microholes is 1200 μm.

[0096] Comparative Example 8 The difference between this comparative example and Example 1 is that the longitudinal depth of the micron-sized micropores is 20 μm.

[0097] Comparative Example 9 The difference between this comparative example and Example 1 is that the longitudinal depth of the micron-sized micropores is 100 μm.

[0098] Comparative Example 10 The difference between this comparative example and Example 1 is that the high-temperature vacuum negative pressure impregnation temperature is 1200°C.

[0099] Comparative Example 11 The difference between this comparative example and Example 1 is that the high-temperature vacuum negative pressure impregnation pressure is -0.6 MPa.

[0100] Test Example 1 (1) XRD test was performed on the Cr3C2-NiCr powder and Cr3C2-NiCr coating in step S11 of Example 1. The results are as follows: Figure 1 As shown in the figure, it can be seen that the phase characteristic peaks of Cr3C2-NiCr powder and Cr3C2-NiCr coating are basically consistent, and no obvious phase change occurs in the Cr3C2-NiCr coating during the preparation process.

[0101] The Cr3C2-NiCr coating in step S11 of Example 1 was analyzed by SEM and EDS. The results are as follows: Figure 2 As shown. Among them, (a) is the SEM micromorphology of the Cr3C2-NiCr coating surface, (b) is the enlarged view of the frame in (a), and (c) is the distribution of Cr and Ni elements in (b); (d) is the SEM micromorphology of the Cr3C2-NiCr coating cross section, (e) is the enlarged view of the frame in (d), and (f) is the distribution of Cr and Ni elements in (e). Figure 2 It can be seen that the overall preparation state of the Cr3C2-NiCr coating is good, the structure is dense, there are no obvious defects such as microcracks and holes, and the elements in the coating are evenly distributed without obvious element segregation and enrichment.

[0102] (2) The composite high-temperature lubricating phase mixture in the modified chromium carbide-based metal ceramic coating prepared in Example 1 was analyzed by SEM and EDS. The results are as follows: Figure 3 As shown, Figure 3 (a) is the SEM image of the composite high-temperature lubricating phase mixture in the modified chromium carbide-based metal ceramic coating, and (b) is the EDS image of the composite high-temperature lubricating phase mixture in the modified chromium carbide-based metal ceramic coating. Figure 3 It can be seen that the mixing state of the three lubricating phase powders (graphite, boron oxide and bismuth oxide) is uniform, without obvious agglomeration phenomenon, and the particle size distribution is consistent.

[0103] The XPS test of the surface of the modified chromium carbide-based metal ceramic coating prepared in Example 1 was carried out, and the results are as follows: Figure 4 As shown, (a) represents the full spectrum of the test area, (b) represents the fine spectrum of the Bi element in the test area, (c) represents the fine spectrum of the B element in the test area, and (d) represents the fine spectrum of the O element in the test area. Figure 4 It can be seen that obvious graphite, boron oxide and bismuth oxide characteristics were detected on the surface of the modified chromium carbide-based metal ceramic coating.

[0104] The surface of the modified chromium carbide-based metal ceramic coating prepared in Example 1 was analyzed by SEM and EDS. The results are as follows: Figure 5 shown. Figure 5 (a) is the SEM image of the surface of the modified chromium carbide-based metal ceramic coating, (b) is the enlarged image of the box in (a), (c) is the EDS image corresponding to (a), and (d) is the EDS image corresponding to (b). Figure 5 It can be seen that the elements of the composite high-temperature lubricating phase mixture are evenly distributed and fully fill the micron-sized pores. The microstructure of the composite high-temperature lubricating phase mixture is dense, with no obvious cracks or pores. The graphite particles are evenly distributed and embedded in the molten boron oxide and bismuth oxide. Boron oxide and bismuth oxide provide significant high-temperature antioxidant protection for the graphite particles.

[0105] Test Example 2 The tribological properties of the modified chromium carbide-based cermet coatings prepared in the following examples and comparative examples were characterized using an HT-1000 high-temperature friction and wear tester. The characterization conditions were as follows: the mode was ball-on-disc, the dual ball was a 5 mm diameter alumina ball, the test used a load of 5 N, a rotation speed of 500 r / min, a rotation radius of 3 mm, and a friction time of 10 min / 30 min. The tribological properties were studied based on the above parameters.

[0106] The friction curves of the modified chromium carbide-based metal ceramic coating of Example 1 at different friction cycle times at 25°C to 800°C are as follows: Figure 6 As shown, Figure 6 (a) corresponds to the result at 25°C, (b) corresponds to the result at 400°C, and (c) corresponds to the result at 800°C. Figure 6 It can be seen that the modified chromium carbide-based cermet coating exhibited a low friction coefficient (approximately COF < 0.2) in four cycles of tribological performance testing at each temperature range. The friction coefficients of the modified chromium carbide-based cermet coating in this embodiment after four cycles at each temperature range of 25°C to 800°C were: 25°C, COF = 0.05; 400°C, COF = 0.11; 800°C, COF = 0.09. The friction coefficient of the composite coating decreased with increasing friction cycles, indicating that a friction lubricating film has formed on the surface of the dual spheres. This composite lubricating phase has significant lubrication properties over a wide temperature range.

[0107] The friction coefficients of the modified chromium carbide-based cermet coating of Example 2 after four cycles at 25°C to 800°C are: 25°C, COF=0.08; 400°C, COF=0.13; 800°C, COF=0.12.

[0108] The friction coefficients of the modified chromium carbide-based cermet coating of Example 3 after four cycles at 25°C to 800°C are: 25°C, COF=0.06; 400°C, COF=0.12; 800°C, COF=0.11.

[0109] The friction coefficients of the modified chromium carbide-based cermet coating of Example 4 after four cycles at 25°C to 800°C are: 25°C, COF=0.05; 400°C, COF=0.18; 800°C, COF=0.13.

[0110] The friction coefficients of the modified chromium carbide-based cermet coating of Example 5 after four cycles at 25°C to 800°C are: 25°C, COF=0.06; 400°C, COF=0.16; 800°C, COF=0.14.

[0111] The friction curve of the modified chromium carbide-based metal ceramic coating of Example 6 after four cycles at 25°C to 800°C is as follows: Figure 7 As shown in the figure, the friction coefficient of the modified chromium carbide-based cermet coating in each temperature range is as follows: 25°C, COF = 0.36; 400°C, COF = 0.69; 800°C, COF = 0.11. This indicates that the modified chromium carbide-based cermet coating has no significant lubrication effect at 25°C to 400°C because it does not have low- to medium-temperature lubrication properties. At 800°C, the low-melting-point oxide lubricating phase is in a glassy state, exhibiting good lubrication.

[0112] The friction coefficients of the modified chromium carbide-based cermet coating of Example 7 after four cycles at 25°C to 800°C are: 25°C, COF=0.09; 400°C, COF=0.14; 800°C, COF=0.12.

[0113] The friction curve of the Cr3C2-NiCr coating of comparative example 1 after four cycles at 25℃~800℃ is as follows: Figure 8 As shown in the figure, the friction coefficient of the Cr3C2-NiCr coating in each temperature range is as follows: 25°C, COF = 0.81; 400°C, COF = 0.46; 800°C, COF = 0.47. This shows that the coating has no lubricating effect in the temperature range of 25°C to 800°C.

[0114] The friction curve of the modified chromium carbide-based metal ceramic coating of Comparative Example 2 after four cycles at 25°C to 800°C is as follows: Figure 9 As shown in the figure, the friction coefficients of the modified chromium carbide-based cermet coating at various temperature ranges are: 25°C, COF = 0.62; 400°C, COF = 0.65; 800°C, COF = 0.49. This indicates that the modified chromium carbide-based cermet coating has no lubricating effect in the temperature range of 25°C to 800°C, and the friction coefficient curve fluctuates violently. This is because the lubricating phase on the coating surface cannot stably exist at the friction interface and cannot stably exert its friction-reducing effect.

[0115] The friction curve of the modified chromium carbide-based metal ceramic coating of Comparative Example 3 after four cycles at 25°C to 800°C is as follows: Figure 10 As shown in the figure, it can be seen that the friction coefficient of the modified chromium carbide-based cermet coating in each temperature range is: 25°C, COF=0.12; 400°C, COF=0.35; 800°C, COF=0.41. This shows that the modified chromium carbide-based cermet coating has a good lubrication effect at 25°C, but as the temperature increases to 400-800°C, its lubrication effect gradually decreases and the friction coefficient increases. This is because low-temperature lubricating phases such as graphite are easily oxidized at high temperatures, resulting in the loss of their lubrication effect.

[0116] The friction coefficients of the modified chromium carbide-based cermet coating of Comparative Example 4 after four cycles at 25°C to 800°C are: 25°C, COF=0.35; 400°C, COF=0.41; 800°C, COF=0.39.

[0117] The friction coefficients of the modified chromium carbide-based cermet coating of Comparative Example 5 after four cycles at 25°C to 800°C are: 25°C, COF=0.33; 400°C, COF=0.42; 800°C, COF=0.44.

[0118] The friction coefficients of the modified chromium carbide-based cermet coating of Comparative Example 6 after four cycles at 25°C to 800°C are: 25°C, COF=0.43; 400°C, COF=0.44; 800°C, COF=0.42.

[0119] The friction coefficients of the modified chromium carbide-based cermet coating of Comparative Example 7 after four cycles at 25°C to 800°C are: 25°C, COF=0.48; 400°C, COF=0.46; 800°C, COF=0.45.

[0120] The friction coefficients of the modified chromium carbide-based cermet coating of Comparative Example 8 after four cycles at 25°C to 800°C are: 25°C, COF=0.51; 400°C, COF=0.48; 800°C, COF=0.49.

[0121] The friction coefficients of the modified chromium carbide-based metal ceramic coating of Comparative Example 9 in each temperature range from 25°C to 800°C are: 25°C, COF=0.39; 400°C, COF=0.36; 800°C, COF=0.38.

[0122] The friction coefficients of the modified chromium carbide-based cermet coating of Comparative Example 10 after four cycles at 25°C to 800°C are: 25°C, COF=0.44; 400°C, COF=0.39; 800°C, COF=0.41.

[0123] The friction coefficients of the modified chromium carbide-based metal ceramic coating of Comparative Example 11 after four cycles at 25°C to 800°C are: 25°C, COF=0.31; 400°C, COF=0.33; 800°C, COF=0.35.

[0124] In summary, the modified chromium carbide-based metal ceramic coating prepared by the method provided by the present invention has both good anti-wear and friction reduction properties. After multi-cycle tribological performance testing in the temperature range of 25°C to 800°C, it shows excellent lubrication performance with a low friction coefficient, which greatly improves the wide temperature range tribological performance of traditional chromium carbide-based metal ceramic coatings and provides an innovative solution for the life extension design of high-temperature moving parts.

[0125] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for preparing a modified chromium carbide-based metal ceramic coating, characterized in that: The following steps are involved: Performing surface texturing pretreatment on a metal substrate having a chromium carbide-based cermet coating to form micron-sized micropores on the surface of the chromium carbide-based cermet coating; Applying a composite high-temperature lubricating phase mixture to the surface of the chromium carbide-based cermet coating having micron-sized micropores, melting the composite high-temperature lubricating phase mixture by high-temperature vacuum negative pressure impregnation and allowing at least a portion of the composite high-temperature lubricating phase mixture to fill the micron-sized micropores; The composite high-temperature lubricating phase mixture includes a high-temperature lubricating phase and a medium-low temperature lubricating phase in a mass ratio of 7.5:2.5 to 8.5:1.5; wherein the high-temperature lubricating phase includes at least one of barium fluoride, calcium fluoride, and hexagonal boron nitride, and the medium-low temperature lubricating phase includes at least two of graphite, boron oxide, bismuth oxide, Ag, Cu, MoS2, and WS2; The conditions for high-temperature vacuum negative pressure impregnation include: temperature of 500°C~1000°C, vacuum degree of -0.5MPa~-0.01MPa.

2. The preparation method according to claim 1, characterized in that The preparation of the metal substrate with the chromium carbide-based cermet coating comprises: using a thermal spraying process to prepare the chromium carbide-based cermet coating on the surface of the metal substrate; Among them, the thermal spraying process includes a low-pressure plasma spraying process, an atmospheric plasma spraying process, a supersonic plasma spraying process or a supersonic flame spraying process.

3. The preparation method according to claim 2, characterized in that The thermal spraying process adopts the supersonic flame spraying process, and the process conditions include: oxygen flow rate of 800L / min~1000L / min, kerosene flow rate of 20L / min~40L / min, carrier gas flow rate of 4L / min~12L / min, and powder feeding rate of 50g / min~120g / min.

4. The preparation method according to claim 1, characterized in that The surface texturing pretreatment method includes at least one of nanosecond laser treatment, picosecond laser treatment, femtosecond laser treatment, cutting and chemical etching.

5. The preparation method according to claim 4, characterized in that The surface texturing pretreatment includes at least one of the following features: Feature 1: Surface texturing pretreatment is performed using nanosecond laser processing. The process conditions include: laser power of 150W~200W, wavelength of 900nm~1100nm, scanning speed of 800mm / s~1000mm / s, and laser irradiation intensity of 0.1J / mm 2 ~0.3J / mm 2 , the process gas includes nitrogen; Feature 2: The center distance between two adjacent micron-sized micropores is 500μm~1000μm; Feature 3: The longitudinal depth of the micron-sized micropores is 40 μm to 80 μm.

6. The preparation method according to claim 1, characterized in that The particle size of the composite high-temperature lubricating phase mixture is 1 μm to 10 μm.

7. A modified chromium carbide-based metal ceramic coating, characterized in that: The product is prepared by the preparation method according to any one of claims 1 to 6.

8. A component, characterized in that: The component has the modified chromium carbide-based metal ceramic coating according to claim 7.

9. Use of the component according to claim 8 in a wear-reducing and wear-resistant mechanical structure.

Citation Information

Patent Citations

  • Metal ceramic composite coating as well as preparation method and application thereof

    CN112281105A

  • Solid lubricant coatings produced by thermal spray methods

    US6689424B1